A description of chloride cell and kidney tubule alterations in the flatfish Solea senegalensis exposed to moderately contaminated sediments from the Sado estuary (Portugal) - Costa, Pedro M. (2021)
The effects of sediment-bound contaminants on kidney and gill chloride cells were surveyed in juvenile Solea senegalensis exposed to fresh sediments collected from three distinct sites of the Sado Estuary (Portugal) in a 28-day laboratorial assay. Sediments were analyzed for metallic contaminants, polycyclic aromatic hydrocarbons and organochlorines as well as for total organic matter, redox potential and fine fraction. The potential for causing adverse biological effects of each surveyed sediment was assessed by comparison of contaminant levels to available guidelines for coastal sediments, namely the Threshold Effects Level (TEL) and the Probable Effects Level (PEL). The Sediment Quality Guideline Quotient indices (SQGQ) were calculated to compare the overall contamination levels of the three stations. A qualitative approach was employed to analyze the histo/cytopathological traits in gill chloride cells and body kidney of fish exposed to each tested sediment for 0, 14 and 28 days. The results showed that sediment contamination can be considered low to moderate and that the least contaminated sediment (from a reference site, with the lowest SQGQ) caused lesser changes in the surveyed organs. However, the most contaminated sediment (by both metallic and organic xenobiotics, with highest SQGQ) was neither responsible for the highest mortality nor for the most pronounced lesions. Exposure to the sediment presenting an intermediate SQGQ, essentially contaminated by organic compounds, caused the highest mortality (48%) and the most severe damage to kidneys, up to full renal necrosis. Chloride cell alterations were similar in fish exposed to the two most contaminated sediments and consisted of a pronounced cellular hypertrophy, likely involving fluid retention and loss of mitochondria. It can be concluded that sediment contamination considered to be low or moderate may be responsible for severe injury to cells and parenchyma involved in the maintenance of osmotic balance, contributing for the high mortality levels observed. The results suggest that sediment-bound organic contaminants such as PAHs (polycyclic aromatic hydrocarbons) and PCBs (polychlorinated biphenyls) may be very toxic to the analyzed organs, especially the kidney, even when present in lowrisk concentrations.